ANALISIS PENDIDIKAN KARAKTER RELIGIUS, PEDULI SOSIAL, DAN PEDULI LINGKUNGAN TERHADAP KEDISIPLINAN (Studi Kasus Mahasiswa Administrasi Perkantoran Politeknik LP3I Jakarta) - Edi Wahyu Wibowo (POLITEKNIK LP3I JAKARTA, 2020)
The impact of globalization that is currently happening has made Indonesians forget their character. There are many problems that arise in Indonesian society, including the case of the lack of character possessed by students. This research analyzes the influence of religious character education, social care, environmental care on discipline of LP3I Jakarta Polytechnic Office Administration students. In the t test, the religious character variable partially does not have a positive and significant effect on the discipline variable. While the Social Care Character variable partially does not have a positive and significant effect on the discipline variable. However, the variable Character Caring for the Environment partially has a positive and significant effect on the discipline variable. In the F test simultaneously or together the independent variables have a significant effect on the dependent variable, that the model is able to explain 41.22% of the dependent variable, while 58.78% is influenced by other factors outside the regression model. For the character of caring for the environment, discipline is good and must be improved. Meanwhile, religious character does not affect discipline, this needs to be increased again in the spirit of learning motivation for religious subjects, it is also necessary to make an appropriate curriculum for religious subjects in order to produce disciplined students. For the character of social care, it is necessary to improve soft skills, especially in terms of sharing, so that students have an increased sense of empathy. This also requires an integrated curriculum between subjects, so that graduates Office Administration program of the Polytechnic LP3I Jakarta, can be ready to work with adequate hard skills and soft skills.Keywords: Character Education, Religious, Social Care, Environmental Care, Discipline